2017
DOI: 10.1159/000468963
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Allograft Injury: An Overview of Pathogenesis and Treatment Strategies

Abstract: Chronic allograft injury (CAI) remains one of the biggest challenges in transplantation as it directly affects the long-term allograft survival, an area in which the scientific and transplantation communities have struggled to improve outcomes. Therefore, understanding the mechanisms of CAI is paramount to implement preventive measures and novel therapeutic options. In this review, we will address the latest evidence on CAI, potential etiologies and risk factors including non-adherence, antibody-mediated rejec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Currently, there are many methods used for promoting fracture healing in clinics [1,2,[10][11][12]. Surgical intervention and autologous bone transplantation are the gold standard of current treatment in the event of fracture nonunion, but the trauma is so large that some patients may need multiple surgeries for years [13][14][15]. Autologous bone is generally taken from the iliac crest or fibula of the patient, which is more damaging to the patient and is prone to infection after sur-gery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there are many methods used for promoting fracture healing in clinics [1,2,[10][11][12]. Surgical intervention and autologous bone transplantation are the gold standard of current treatment in the event of fracture nonunion, but the trauma is so large that some patients may need multiple surgeries for years [13][14][15]. Autologous bone is generally taken from the iliac crest or fibula of the patient, which is more damaging to the patient and is prone to infection after sur-gery.…”
Section: Introductionmentioning
confidence: 99%
“…The cell components in allogeneic bones are mostly dead and do not have their own osteogenic ability. Studies have found that allogeneic bone treatment for nonunion fractures takes about 12 months for allogeneic bone surface union; indeed, internal osteogenesis is very slow, occurring at a rate of only 15-20% within five years, and deep repair hardly occurs [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The risk of de novo DSA after transplantation includes nonadherence, immunosuppression minimization, young recipient, CYP3A5 expressor, recipient with HLA mismatch or high panel reactive antibody, history of previous kidney transplantation, prolonged ischemic time, history of T-cellmediated rejection, and history of allograft inflammation from viral infection [7,13,14 ]. Minimization of de novo DSA risk can prevent patients from developing chronic ABMR which is one of the most important causes of late allograft dysfunction [15].…”
Section: Prevention Of Donor-specific Antibody Developmentmentioning
confidence: 99%
“…(Madariaga and Riella, 2017;Naesens et al, 2009;Riella et al, 2017) In the BENEFIT trial, where a CNIavoidance regimen (co-stimulatory blockade with Belatacept) is compared to the more standard CNI-based regimen (cyclosporine), Vincenti et.al. showed improved long-term renal allograft function over a follow-up period of 7 years with CNI-avoidance in selected patients ( Figure 1.11).…”
Section: Calcineurin Inhibitor Toxicity Impacts On Long-term Allografmentioning
confidence: 99%